2012
DOI: 10.1038/nature10710
|View full text |Cite
|
Sign up to set email alerts
|

Tail-assisted pitch control in lizards, robots and dinosaurs

Abstract: In 1969, a palaeontologist proposed that theropod dinosaurs used their tails as dynamic stabilizers during rapid or irregular movements, contributing to their depiction as active and agile predators. Since then the inertia of swinging appendages has been implicated in stabilizing human walking, aiding acrobatic manoeuvres by primates and rodents, and enabling cats to balance on branches. Recent studies on geckos suggest that active tail stabilization occurs during climbing, righting and gliding. By contrast, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
208
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(216 citation statements)
references
References 21 publications
5
208
0
3
Order By: Relevance
“…Besides adjusting the centre of mass (CoM) close to the vector of propulsive thrust at take-off to avoid later body rotation [7,8], some jumpers actively use dynamic control for in-air stability. Two mechanisms have previously been proposed to counteract unwanted torque in the air: using the inertia of swinging appendages [9][10][11][12] and aerodynamic forces from flapping wings [6,7]. Take-off mechanisms and stability control that evolved in nature have led to significant progress in bioinspired designs for manoeuvrable jumping robots [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Besides adjusting the centre of mass (CoM) close to the vector of propulsive thrust at take-off to avoid later body rotation [7,8], some jumpers actively use dynamic control for in-air stability. Two mechanisms have previously been proposed to counteract unwanted torque in the air: using the inertia of swinging appendages [9][10][11][12] and aerodynamic forces from flapping wings [6,7]. Take-off mechanisms and stability control that evolved in nature have led to significant progress in bioinspired designs for manoeuvrable jumping robots [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…They were both chosen because of a clear IMRD-structure and because they aligned nicely with most of the students building a robot with a specified task in the semester project. The third research paper compares the tail-assisted pitch control in lizards, robots and dinosaurs and was published as a letter in Nature a few years ago [37]. Hence this paper does not follow the normal IMRD-format, but was chosen merely because of its relevance for the students' semester projects and for the stimulating and intriguing topic.…”
Section: Use Of Authentic Research Papersmentioning
confidence: 99%
“…Nonetheless there are some notable exceptions: kangaroo rats and pocket mice have been observed performing precise aerial maneuvering using their tail (Bartholomew and Caswell, 1951;Hickman, 1979). Geckos and other lizards have also been shown to use their tails extensively for aerial posture-control, particularly for controlling body-pitch (Jusufi et al, 2008;Libby et al, 2012) and the concept has been demonstrated to be useful in robotics as well (Johnson et al, 2012;Libby et al, 2012;Liu et al, 2014). Among larger terrestrial mammals, cheetahs appear to use their rather large tails to aid in cornering at high speeds, a concept that has been recently explored in robotics (Briggs et al, 2012;Patel and Braae, 2013).…”
Section: Introductionmentioning
confidence: 99%